ON THE ISSUE OF INFORMATION AND ANALYTICAL SUPPORT OF THE LEGAL WORK OF THE STATE TAX SERVICE - Vadym O. Anokhin (Alfred Nobel University Journal of Law)
The article is devoted to one of the areas of comprehensive research on information and analytical support of legal work in the bodies of the state tax service. The article provides an analysis of the achievements of scientists whose research was the organization of legal work in state bodies in general, and tax bodies in particular, as well as studies of scientists whose activities are related to the formation of information law. The work also focuses on the project approach effectiveness in terms of providing information to the legal units of the state tax service through the creation of automated information systems and automated lawyer workplaces. In addition to ascertaining the fact, the information system of the state tax service bodies is characterized by multi-source, multi- segmentation and an excessive number of documents with varying degrees of access, importance and complexity. The need is substantiated for a quick response by the tax authority to any changes in all economic and legal processes of the state. In particular, it needs for regarding the fast acquiring of information from various sources, its generalization and processing. The proposed article mentions the beginning of the creation, development and use of databases and automated information systems in the tax authority police units as an example of removing obstacles that prevent the effective exchange of information with other law enforcement and state control and management bodies. As a result of the analysis, a number of factors that negatively affect the information support of the tax service's legal work, its cooperation with other law enforcement agencies, were revealed. The work also presents the factors that determined the automation of the legal work of the state tax service bodies, highlighting three levels of concentric presentation of the methodology model with the corresponding conclusions. The result of the study is the identification of factors that influence the improvement of legal regulation of managerial relations.